Antibacterial activity extracts of the ant genera crematogaster and solenopsis (2013)
One of the main problems faced today by the scientific community is the increasingly frequent occurrence of pathogenic bacterial strains resistant to current antibiotics and antimicrobial, because these germs are able, under certain circumstances, to be immune to such chemicals, it is therefore necessary to pursue the search for new agents. For this purpose, a good source can come from social insects, which have developed as a survival strategy, the production of bactericidal agents to protect their colonies. The purpose of this work was to determine if certain ants that have adapted to urban environments, have antibacterial activity and to what extent. For this purpose, ants of the genus Crematogaster sp. and sp. Solenopsis were captured and subjected to extraction process by maceration, yielding total ethanolic extracts, very little soluble, which were evaluated at different concentrations on Gram negative bacteria strains (Klebsiella pneumoniae and Pseudomona aeruginosa) and Gram positive (Bacillus subtilis spizizenii and Staphylococcus aureus), finding growth inhibitory activity at different degrees over all strains, including an S. aureus one resistant to antibiotics Amoxicillin/Clavulanate, Ampicillin/Sulbactam, Ceftriaxone and Oxacillin; therefore, these species can be classified as promising in the search for new antimicrobial agents.